Black male outsider : teaching as a pro-feminist man : a memoir - Lemons, Gary L. (State University of New York Press, 2008)
"This book traces the development of the author's consciousness as a black male pro-feminist professor. Gary L. Lemons explores the meaning of black male feminism by examining his experiences at the New York City college where he taught for more than a decade - a small, private, liberal arts college where the majority of the students were white and female. Through a series of classroom case studies, he presents the transformative power of memoir writing as a strategic tool for enabling students to understand the critical relationship between the personal and the political. From the insightful inclusion of his own personal narratives about his childhood experience of domestic violence, to stories about being a student and teacher in majority white classrooms for most of his life, Lemons takes the leader on a provocative journey about what it means to be black, male, and pro-feminist."--Jacket